2021
DOI: 10.3390/cells10102515
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation Suppresses IFNγ-Mediated PD-L1 and MCL1 Expression in EGFR-Positive Lung Cancer to Augment CD8+ T Cells Cytotoxicity

Abstract: Tumor cells express immune checkpoints to exhaust CD8+ T cells. Irradiation damages tumor cells and augments tumor immunotherapy in clinical applications. However, the radiotherapy-mediated molecular mechanism affecting CD8+ T cell activity remains elusive. We aimed to uncover the mechanism of radiotherapy augmenting cytotoxic CD8+ T cells in non-small-cell lung cancer (NSCLC). EGFR-positive NSCLC cell lines were co-cultured with CD8+ T cells from healthy volunteers. Tumor cell viability and apoptosis were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…PBMCs from blood samples were isolated using centrifugation by Ficoll-Paque PLUS media (Cytiva, Marlborough, MA, US) as previously described [ 34 ]. In short, 10 mL of whole blood from each healthy donor and 3 mL of whole blood from each patient were centrifuged at 1200 rpm for 30 min without braking to isolate 3 mL of buffy coats.…”
Section: Methodsmentioning
confidence: 99%
“…PBMCs from blood samples were isolated using centrifugation by Ficoll-Paque PLUS media (Cytiva, Marlborough, MA, US) as previously described [ 34 ]. In short, 10 mL of whole blood from each healthy donor and 3 mL of whole blood from each patient were centrifuged at 1200 rpm for 30 min without braking to isolate 3 mL of buffy coats.…”
Section: Methodsmentioning
confidence: 99%
“…This is a nice example of how a systemic effect does not necessarily translate in a similar manner intratumorally ( 94 ). To study the mechanism by which irradiation is affecting the immune cells in the tumor microenvironment, Wang et al ( 95 ), performed in vitro experiments with NSCLC cell lines and CD8+ T cells from healthy donors. Contradictory to in vivo results that show an increase in PD-L1 expression in cancer cells, here they concluded that irradiation (IR) is augmenting CD8+ T cells immunity by suppressing PD-L1 expression in an IFNγ related manner.…”
Section: Immune Landscape and Radiotherapymentioning
confidence: 99%